The Bahamas : 2009 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for The Bahamas's 2009 Article IV Consultation examines economic developments and policies. The financial sector, including the offshore sector, accounts for about 20 percent of economic activity. Exchange controls are maintained on capital transactions, narrowing the field of investment opportunities for local wealth, largely to real estate and government debt. Macroeconomic policy has historically been geared to maintaining fiscal sustainability, attracting investment, and supporting the exchange rate peg.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet